2021
DOI: 10.1177/00469580211025209
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Views on Lifestyle Intervention Program Enhancing Long-Term Health-Related Behaviors Improvement among Prehypertension and/or Prediabetes Mellitus Older Adults: A Qualitative Study Examined in Thailand at Health Promoting Hospitals

Abstract: This study aimed to investigate the view of prediabetes and prehypertension elderly patients living around temple on long-term self-management in proficient way underneath the lifestyle intervention program based on both focus-group discussion and In-depth interview methods to fill the gap in partially successful intervention. 62 participants were selected from 220 participants of the quantitative published study by 2 researchers. The triangulation method was used to put great emphasis on the consistency and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Having family members join group activities has shown to improve glycemic control, diabetes knowledge, self-efficacy and quality of life (37,(45)(46)(47). While family can be both a barrier and facilitator for lifestyle changes, their influence is substantial, especially in Asian cultures, and hence family should be included as agents of change in any proposed intervention (44,(48)(49)(50)(51)(52)(53)(54)(55). In addition to program-related factors, inadequate comprehension of requisite program components (e.g., metformin) were important determinants hindering participation.…”
Section: Discussionmentioning
confidence: 99%
“…Having family members join group activities has shown to improve glycemic control, diabetes knowledge, self-efficacy and quality of life (37,(45)(46)(47). While family can be both a barrier and facilitator for lifestyle changes, their influence is substantial, especially in Asian cultures, and hence family should be included as agents of change in any proposed intervention (44,(48)(49)(50)(51)(52)(53)(54)(55). In addition to program-related factors, inadequate comprehension of requisite program components (e.g., metformin) were important determinants hindering participation.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a healthy lifestyle, including nutrition, physical activity, cognitive and social participation, and metabolic and vascular risk monitoring are known to be important in reducing the risk of cognitive decline and disability [38]. It is also reported that the intervention program, including these lifestyle factors, promoted balanced nutrition habits, exercise, and social participation of older adults, improving their quality of life [39]. Lifestyle intervention is increasingly emerging as an important goal for preventing dementia and depression, promoting health in the older adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…Believing and following health providers has a positive side, as it is easy to invite them to participate in interventions, but this could entail a risk of not matching the needs of older adults and cause them to be passive consumers. There are several studies about using programmes that tended to be of the kind that motivated individual older adults to improve their daily lifestyle, such as a study using the Physical Activity Intervention Programme [ 23 ], the Intervention Programme for Depressive Symptoms [ 24 ], and the lifestyle intervention programme enhancing long-term health-related behaviour improvement [ 25 ]. However, all the programmes mentioned in previous studies were operated by staff that acted as coaches and educators and lacked initiatives from older adults themselves.…”
Section: Introductionmentioning
confidence: 99%